Children’s Influence on Family Purchase Decision in Pokhara - Palikhe, Amin; Lungeli , Milan Magar (Journal of Nepalese Business Studies, 2024)
This article assesses the children’s influence on family purchase decision during the purchase of goods and services that explains major influence in purchasing decisions within the family. The main purpose of the study is to understand the relationship between factors of children’s influence on family purchase decisions. The social learning theory is used to link the factors that determine the influence of children and, after reviewing various relevant studies, the conceptual framework is developed. The study has used descriptive, explanatory design and quantitative in nature. The sources of data collection are the primary sources. Structured questionnaires are used to know the opinions of parents on their children’s influence on family purchase decisions. For the purposes of this survey, total 140 respondents (parents) are sampled by using convenience sampling method. The data collected from the questionnaire has been analyzed and interpreted with the help of SPSS 20 version to analysis the children’s influence on family purchase decision. The regression and correlation method has been employed to show the impact and correlation between the dependent and independent variables. The analysis revealed that children have significant influence on family purchase decisions, particularly in categories like durable, vacations, movies, eating. Moreover, types of products and peer influence are playing important role on family purchase decision. The findings reveal to a better understanding of the complex family buying behavior, offer valuable and insightful information for marketers to target family-oriented consumers.